The British immigration courts a study of law and politics - Travers, Max 1961- (Policy Press, 1999)
Immigration has been a controversial and contentious area of public policy since the Commonwealth Immigration Act ended most primary immigration in 1962. This study looks in detail at the work of practioners in the court-system that hear appeals from immigrants and asylum seekers against decisions made by the British Government. The book contains chapters about decision making in primary purpose and the asylum appeals, the administrative problems faced by successive British governments, and the perspectives of pressure groups and politicians. The British Immigration Courts transforms our understanding of immigration as a political issue through preserving a sense of routine work in the courts, civil service and political process which is ignored or idealised by other approaches. It is essential reading for practioners, academics and students interested in current debates about policy
Title from publisher's bibliographic system (viewed on 22 Jul 2022)
Keywords: Emigration and immigration law / Great Britain; Asylum, Right of / Great Britain; Administrative courts / Great Britain; Immigration courts; Great Britain / Emigration and immigration